Foreign Body in the Cervical Oesophagus: A Case Report - Giordano, Davide; Botti, Cecilia; Iotti, Valentina; Ghidini, Angelo (Current Medical Imaging, 2022)
Background: Foreign bodies in the upper aerodigestive tract represent an uncommon cause of visits to emergency departments. In the majority of cases, foreign bodies do not go beyond the pharynx. They cause dyspnoea or pneumonia if they reach the tracheobronchial tree. If ingested, they will pass spontaneously through the gastrointestinal canal in the majority of cases. Nevertheless, especially in the case of sharp-pointed or large objects, the foreign bodies can stop in the oesophagus. In case of dysphagia, stinging sensation and/or odynophagia occurring after eating a meal, a foreign body in the upper aerodigestive tract should be suspected. If not clinically visible, imaging is required. Case Presentation: A 72-year-old woman presented to the Emergency Department with pharyngodynia, odynophagia, stinging, dysphagia, and sialorrhea for 12 hours. Her symptoms started after eating a meal involving meat. The patient underwent a standard two-projection radiogram of the neck. The antero-posterior projection radiogram was unremarkable. The lateral projection radiogram showed 16 millimetres in maximum length radiopaque foreign body within the cervical oesophagus. The patient underwent transoral flexible oesophagoscopy under general anaesthesia, which resulted in successful removal of the foreign body (bony fragment). Her symptoms improved rapidly after the procedure, and the patient was discharged after 48 hours in good health. Conclusion: A foreign body in the cervical oesophagus may lead to visceral perforation. Once suspected, every effort should be made to identify and remove the foreign body to avoid potentially catastrophic consequences. In some cases, imaging could be necessary to detect the foreign body.
Keywords: oesophagus